Intoxication syndrome in patients with pulmonary tuberculosis in relation to the system glutathione transferase gene polymorphism - N. A. Stepanova; Kh. M. Galimzyanov; B. I. Kantemirova (Журнал инфектологии, 2017)
In 178 patients with different clinical forms of pulmonary tuberculosis carried out pharmacogenetic testing to determine gene polymorphism glutathione S-transferase system (GSTM1, GSTT1). Estimated the severity and duration of clinical manifestations of the syndrome of intoxication, depending on the gene polymorphism of glutathione S-transferase system (GSTM1, GSTT1). It was found that the combination of “zero” to develop genotypes GSTM1 and GSTT1 enzyme is a predictor of the severity and duration of symptoms of intoxication persisting.